Prolactin Receptor Gene Exon 9 Polymorphism in Surti and Jaffarabadi Buffaloes - Devkatte, Savita; Janmeda, Mamta; Ramani, Umed; Patel, Santul; Dangar, Nikhil; Kharadi, Vishnu; Pandya, Gaurav (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
Molecular genetic analysis of quantitative traits leads to a better understanding of genes governing milk yield and the composition of traits. Prolactin (PRL) acts through its receptor PRLR via both endocrine and local paracrine/autocrine pathways to regulate biological processes including production and reproduction. The present study was undertaken with the objective to amplify Prolactin Receptor (PRLR) gene exon nine regions using bovine specific primers using Polymerase Chain Reaction-restriction Fragment Length Polymorphism (PCR-RFLP) in Surti and Jaffarabadi buffaloes. A total of 50 Surti and 50 Jaffarabadi buffaloes were screened for polymorphism in 582 bp exon 9 of PRLR gene and observed three genotypes AA (582 bp), heterozygous AG (582,399,183 bp) and GG (399, 183 bp) in Surti buffaloes with genotypic frequencies of 0.48, 0.44 and 0.08 for AA, AG and GG genotypes and gene frequencies for A and G alleles were 0.70 and 0.30, respectively. The Jaffarabadi buffaloes PCR-RFLP pattern revealed two genotypes with genotypic frequencies 0.44 and 0.56 for AA and AG genotypes with absence of GG genotype and gene frequencies for A and G 0.72 and 0.28, respectively. Association study of PRLR/DraIII genotypes with milk production traits gave non-significant results.